Weed Incursion of Irrigated Forage–Forb Mixtures Under Mob Grazing or Mowing in the Mountain West USA - Jennifer MacAdam; Jared Gibbons; Xin Dai (Agronomy)
Improving the quality of irrigated pastures can increase the profitability of ruminant production systems. Increasing pasture plant biodiversity is beneficial for ruminants, pollinators, and soil health, but it is challenging to manage weed incursion in seeded mixed-species pastures. This study assessed the weed incursion that resulted when forage legumes or grasses were seeded as binary mixtures with one of four non-legume forbs. Defoliation occurred at 6-week intervals as either mowing or mob grazing. Forbs were chicory, plantain, Lewis flax, or small burnet and forages were alfalfa, birdsfoot trefoil, creeping foxtail, intermediate wheatgrass, kura clover, meadow bromegrass, orchardgrass, perennial ryegrass, reed canarygrass, sainfoin, smooth bromegrass, tall fescue, and white clover. Four defoliations per year occurred between May and September for two years. Eight replications were grouped into four blocks and each pair in a block was randomly assigned to the two defoliation treatments, mob grazing or mowing. Plots were 1.5 m2 and were assessed visually before each defoliation for the percentage of forage, forb, and weed. Chicory was the most dominant of the four forbs, and relative to legumes, most grasses suppressed both forb establishment and weed incursion under both grazing and mowing. There were no statistically significant effects of defoliation treatment on weed incursion.